Peranan Kualitas Website dan Aplikasi Youtube sebagai Media Komunikasi Pemasaran Terpadu dalam Mempengaruhi Pergeseran Perilaku Konsumen - Dadah Muliansyah; Rima Rahmayanti (Journal of Information Technology, 2019)
In the current era of communication globalization, the role of social media is needed by humans to interact with each other. Social media is a medium for socializing with each other online, which allows users to interact with each other without being limited by time and space. This social media has a big influence on society especially young people who are the main consumers. The influence of social media as a marketing communication media, where users can give opinions and provide information to each other. On the other hand social media can also change the character of consumers, especially teenagers who are unstable and tend to be easily influenced. This study examines the role of websites and YouTube in influencing the character of consumers in buying products or services. The research population was selected by University Students in Bandung and 100 (one hundred) students were taken at University X in Bandung who were active in social media. The results of the questionnaire were processed using the partial least square method.